Three critical questions for future research on lesbian relationships. Issue 1 (2nd January 2017) - Diamond, Lisa M.
ABSTRACT: In this article I discuss three questions that should be priorities for future research on lesbian love and relationships. The first question concerns the very definition of "lesbian relationship, " given how many women may be engaged in same-sex relationships without identifying as lesbian. The second question concerns the potential influence of childhood neglect and abuse on adult women's same-sex relationships, a topic that has important implications for both psychological well-being and relationship functioning. The third question concerns the potential downsides of legal marriage for women's same-sex relationships, a topic that is particularly important in light of the newfound legal recognition of same-sex marriage in all 50 states. Although there are many understudied questions in the domain of women's same-sex relationships, research on these three questions has particularly strong potential to advance our understanding of lesbian love and relationships in important ways.